Integrating STEAM and multimodal digital prompts for grade 5 creative poetry writing - Iis Aprinawati; Nurmalina Nurmalina; Hatice Ergul (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This qualitative descriptive–exploratory study documents the enactment of STEAM-oriented language arts instruction, supported by LCD-projected multimodal digital prompts, to scaffold Grade 5 creative poetry writing in one Indonesian elementary classroom. Addressing limited operational clarity in prior studies on digital media for poetry learning, particularly regarding stage-specific prompt functions and replicable sequencing, the study contributes a six-session instructional model specifying how prompts support observation, drafting, and revision. Data were drawn from classroom observations, semi-structured interviews with teachers and students, and analysis of poetry artefacts; a 1–4 rubric (diction, imagery, thematic alignment, originality) was used strictly for descriptive profiling. Findings are reported as data-grounded patterns: participants described prompts as useful entry points for initiating writing and elaborating imagery, while artefact excerpts indicate movement from general evaluative phrasing toward more specific sensory and figurative language, with variation across students. Interpretations remain bound to the single-classroom context and do not constitute causal or comparative claims.